The Worker and the Constitution: A Theory of Constitutional Labour Law - Eustace, Alan (Trinity College Dublin. School of Law. Discipline of Law, 2023)
This thesis constructs a theoretical justification for the phenomenon of ?constitutional labour law? ? that is, legal decisions about the interaction between constitutional norms, including human rights, and the labour relationship. Specifically, it answers the research questions of: why and how should courts intervene in the labour relationship on the basis of constitutional norms? It examines existing literature on this subject, which approaches the question from the perspectives of ?labour rights are human rights? and ?human rights at work?, concluding that neither perspective adequately explains and justifies constitutional labour law. Therefore, a new theory is needed that will be more descriptively convincing, and more normatively compelling, to fill this ?justification gap?. The thesis argues that the concept of citizenship gives us a normative basis for making legal decisions about the interaction between constitutional norms and the labour relationship, providing theoretically robust answers to the central research questions. The ability of workers to function as citizens outside the workplace is influenced by what goes on in the workplace and by their relationship with an employer. The condition of ?submission and subordination? to which workers are subject on a day-to-day basis inhibits them from nurturing the ?habits of democracy? necessary to function as citizens. Moreover, workers are dissuaded from exercising their political and civic rights out of fear of the consequences should their employer find out, disagree, and impose sanctions on them. There is a risk workers will only exercise their political rights in ways that benefits their employers? ends and interests, diminishing the political power of workers, and enhancing that of employers. That leads to the systemic disenfranchisement of workers and potential capture of state institutions by employers. Constitutional labour law should be a means to prevent liberal democracy sliding towards plutocracy. Finally, the thesis develops a doctrinal programme for constitutional labour law. Constitutional labour law must provide for: worker organisation, representation, participation and fair procedures in decision-making; dedicated public labour-related decision-making institutions and processes; and protection for civil liberties at work and against discrimination. Rights granted to workers in each of these areas must be capable of overriding provisions in even freely-agreed contracts of employment to the contrary, because there is a public interest basis for their protection that would be undermined by individual waivers. These rights must apply even against private employers, because of the threat private power can pose to workers? citizenship. The practical requirements can be summed up in the themes of participation and political independence. The thesis examines case law from Ireland and the European Court of Human Rights to draw lessons on the implementation of these values. It uses Irish constitutional jurisprudence to illustrate practical issues in respect of participation internal to the workplace ? both collective in the form of trade union activity, and individual in the form of fair procedures ? and outside the workplace, in the form of subsidiary regulatory institutions. It then draws on case law from the European Court of Human Rights to illustrate the sorts of ?civil liberties? issues that crop up in constitutional labour law: freedom of expression, the free practice of religion or philosophical belief, and privacy; and how to balance and adapt these rights in the context of employment.
APPROVED
Keywords: Constitutional law; Constitutional theory; Labour law; Trade unions; Industrial relations; Civil liberties; Constitutional labour law